Implementasi Bacaan Al-Quran Metode Qiro’ati terhadap Hafalan Al-Qur’an Santri di Lingkungan Pesantren: (Studi Kasus Faktor Pendukung dan Hambatan Siswa dalam Program Tahfidzul Qur'an di SMP Daruttaqwa Full Day School Gresik) - Muhammad Irham; H. Mustadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The Qiroati method is an instructional approach to reading the Qur’an that emphasizes direct practice of tartil recitation in accordance with the rules of tajwid. This method is practical, systematic, and implemented gradually, meaning that learners are not allowed to proceed to the next level before achieving fluency at the current stage. One of the main challenges in learning to read and memorize the Qur’an is the limited use of structured teaching methods, as some teachers still rely primarily on personal experience and conventional reading approaches. This condition contributes to students’ lack of fluency in reading and memorizing the Qur’an, as well as decreased learning motivation due to monotonous and less effective instructional practices. This study aims to examine the implementation of the Qiroati method in improving students’ Qur’anic reading ability within the Tahfidzul Qur’an program at SMP Daruttaqwa Full Day School. The findings are expected to provide useful insights for educators and contribute to academic knowledge. This research employs a field research design with a descriptive qualitative approach, focusing on describing the application of the Qiroati method in enhancing students’ reading ability in relation to Qur’an memorization. Data were collected through interviews, tests, and documentation, while data analysis involved data collection, data display, and conclusion drawing. The results indicate that the implementation of the Qiroati method effectively improves students’ ability to read the Qur’an in the Tahfidzul Qur’an program. This is evidenced by the improvement in students’ reading scores compared to their previous performance. In practice, the method involves teachers modeling correct recitation, followed by students reading collectively. Therefore, the Qiroati method not only enhances students’ accuracy in reading the Qur’an but also fosters a more engaging and effective learning environment.